Prostate Cancer Monitoring using MRI Monomodal Feature-Based Registration - Aisyah Rahimi; Azira Khalil; Farisha Noordin; Khin Wee Lai; Shahrina Ismail; Muhammad Mokhzaini Azizan (MALAYSIAN INSTITUTE OF PHYSICS, 2024)
Volume 43 Issue 1 (2022) Page (10167-10177)